2019
DOI: 10.1007/s13197-019-03768-9
|View full text |Cite
|
Sign up to set email alerts
|

Profile of chlorophylls and carotenoids of wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) microgreens

Abstract: The use of cereal microgreens is increasing because of increased consumer's interest in healthier products. Chlorophyll (Chl) and Carotenoids (Car) are suggested to correlate with health promoting components like phenolics and antioxidant potential of the plant-part. They also play role against clinical conditions like thalassemia and hemolytic anemia and reduce the risk of some chronic diseases, such as cancer, cardiovascular diseases, skin diseases and age-related eye diseases. This study was carried out for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 32 publications
5
35
3
2
Order By: Relevance
“…Niroula et al. () found that carotenoid content increased in wheat and barley microgreens over the course of the 16‐day growth period studied. The rate of accumulation slowed between 7 and 10 days in wheat and between 10 and 13 days in barley, but maximum values were obtained on the last harvesting day.…”
Section: Microgreen Nutrient Contentmentioning
confidence: 96%
“…Niroula et al. () found that carotenoid content increased in wheat and barley microgreens over the course of the 16‐day growth period studied. The rate of accumulation slowed between 7 and 10 days in wheat and between 10 and 13 days in barley, but maximum values were obtained on the last harvesting day.…”
Section: Microgreen Nutrient Contentmentioning
confidence: 96%
“…However, it is now being increasingly considered to possess high nutritional value and antioxidant properties and thus, draws increasing attention due to the health benefits associated with it [1]. Indeed, barley grass is currently considered a health product, as many studies have demonstrated its potential in treating human chronic diseases [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins have a major role in the growth and maintenance of the human body, and barley grass contains 20 amino acids involved in energy production, and cell building and regeneration [3]. Furthermore, barley grass is rich in pigments, which mainly include chlorophyll (Chl) and carotenoids (Car) [2]. The Chl t content in barley grass is sufficiently high to exert potential health benefits in humans; thus, a daily intake of 100-300 mg of Chl t has been demonstrated to be beneficial for the treatment of various diseases in humans, including cancer [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations